2011
DOI: 10.1128/mcb.00470-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PITX1 as a TERT Suppressor Gene Located on Human Chromosome 5

Abstract: Telomerase, a ribonucleoprotein enzyme that maintains telomere length, is crucial for cellular immortalization and cancer progression. Telomerase activity is attributed primarily to the expression of telomerase reverse transcriptase (TERT). Using microcell-mediated chromosome transfer (MMCT) into the mouse melanoma cell line B16F10, we previously found that human chromosome 5 carries a gene, or genes, that can negatively regulate TERT expression (H. Kugoh, K. Shigenami, K. Funaki, J. Barrett, and M. Oshimura, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 56 publications
(76 reference statements)
2
81
0
Order By: Relevance
“…The present study demonstrated that the expression of PITX1 was downregulated in HNSCC samples compared with that in normal pharyngeal samples, suggesting that PITX1 may act as a tumor suppressor and a possible novel biomarker in HNSCC and other human malignancies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). A previous study demonstrated that a low expression of PITX1 is associated with a poor prognosis in colorectal carcinoma (16) and hepatocellular carcinoma (15).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The present study demonstrated that the expression of PITX1 was downregulated in HNSCC samples compared with that in normal pharyngeal samples, suggesting that PITX1 may act as a tumor suppressor and a possible novel biomarker in HNSCC and other human malignancies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). A previous study demonstrated that a low expression of PITX1 is associated with a poor prognosis in colorectal carcinoma (16) and hepatocellular carcinoma (15).…”
Section: Discussionsupporting
confidence: 50%
“…Amplification of unmutated KRAS2 in HNSCC contributes to tumor growth (28). It was also reported that PITX1 suppresses TERT by directly binding to the TERT promoter (8), which is known to be a component of the telomerase enzyme and is necessary for cancer cell immortalization and proliferation (29). Previously, Ohira et al (30) reported that the mRNA expression level of PITX1 is directly suppressed by microRNA-19b, followed by the upregulation of TERT expression in melanoma cells (30).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5A). Furthermore, PITX1 has been identified as a tumor suppressor and is associated with the progression and development in various cancers (21)(22)(23)(24)(25).…”
Section: Mir-886-3p Targets the Tumor Suppressor Gene Pitx1mentioning
confidence: 99%
“…This technique has been used for the identification of genes related to tumor suppression [13,14], genomic imprinting [15,16], DNA repair [17][18][19], metastasis and genomic instability [20], telomerase regulation [21][22][23], mitochondrial disorders [24], and lysosomal storage diseases [25]. MMCT has also been applied to investigate chromosomal functions such as kinetochore assembly, telomere function, and high-order chromosome architecture [8,26,27].…”
Section: Applications Of Mmct and The Hurdles Of Conventional Genomementioning
confidence: 99%